Small-sided games are more effective than instructional training for improving vertical jump performance and passing in young volleyball players - Damir Pekas; Draženka Mačak; Anja Kostić Zobenica (Exercise and Quality of Life, 2019)
The aim of our research was to determine the effects of small-sided games on explosive strength in young volleyball players. The authors hypothesized that this program might significantly improve explosive strength in adolescent volleyball players. Thirty-eight adolescent volleyball players participated in this study (12.26±1.01). They were tested for lower body explosive power and passing accuracy. Players were randomly allocated into a small-sided games group (n = 20) and instructional training group (n = 18). Each player participated in a 12-week training program that included 3 organized court training sessions per week. Both groups made significant increases in block jump (p < 0.05) after 12 weeks of training, with significant interaction effect between the groups. There were no significant interaction effects between the groups (p>0.05) for spike jump. In SJ and CMJ results revealed a statistically significant difference between groups pre- to post- training (p < 0.05). Both groups made significant increases in passing accuracy with significant interaction effect between the groups. Small-sided games appears to be an effective way of improving explosive power and passing skills in young volleyball players. The results of this study indicate that game-based training method was more effective for lower body explosive power than traditional instructional programme.